Quality Assurance Practices And Teachers’ Effectiveness In Public Senior Secondary Schools In Kwara State Nigeria - Olaifa, Adeseko Sunday; Jolaoye, Joshua Durotoye; Ayoku, Oba Baba; Shittu, Afeez Adeshina (International Journal of Instructional Technology, 2022)
The success of a nation relies heavily on the quality of teachers and their efforts. To improve educational standards, efforts should focus on teachers' effectiveness. However, inadequate facilities and lack of training hinder teachers' effectiveness in public senior secondary schools. This study aims to examine the predominant quality assurance practices, determine teachers' effectiveness, and investigate the relationship between these practices and teachers' effectiveness in Kwara State public schools. The study used a descriptive survey design to survey 7700 teachers in Kwara State's public senior secondary schools. The Krejcie and Morgan table was used to select 367 respondents. Data was collected using the Quality Assurance Practice Questionnaire (QAPQ) and Teachers' Effectiveness Questionnaire (TEQ), with reliability coefficients of 0.74 and 0.71 using the Cronbach Alpa method. The study found that evaluation was the most commonly used quality assurance practice in public senior secondary schools in Kwara State (3.16%). Teachers' effectiveness was high (3.05%), and there was a significant relationship between quality assurance practices and teachers' effectiveness (F=0.474; p< 0.05). The study concluded that teachers' effectiveness is largely dependent on the full usage of quality assurance practices such as capacity building, supervision, physical facilities, and accreditation. The sustainability of these practices will increase teachers' effectiveness. It was recommended that the level of quality assurance practices should be above moderate, with regular capacity building, supervision, physical facilities and accreditation.